# Solve the equation-

5h-9=-16+6h

## Subtract 5h and add 16 to both sides.

This is because...
5h-9= -16+6h
first step is to get the H's together on one side so you subtract 5h from 5h and 6h to get....
-9= -16+h
once you are here you want to the the numbers on one side like we did for the H's, so you add 16 to -9 and -16
7=h!

And that is how you get your answer 7=h! This is very easy and simple pre-algebra. You should have no problem solving this. Please pay attention during class so you get better grades! <3

## To solve the equation 5h - 9 = -16 + 6h, you need to isolate the variable 'h'. Here's how you can do it step by step:

Step 1: Start by simplifying both sides of the equation:
5h - 9 = -16 + 6h

Combine like terms:
5h - 6h - 9 = -16

Simplify further:
-h - 9 = -16

Step 2: Next, move all terms containing 'h' to one side of the equation. To do this, you can add 'h' to both sides of the equation:
-h + h - 9 = -16 + h

Simplify further:
-9 = -16 + h

Step 3: Now, rearrange the equation by adding 16 to both sides:
-9 + 16 = h

Simplify further:
7 = h

So, the solution to the equation is h = 7.